Respuesta :

Step-by-step explanation:

[tex] \frac{ {a} + 4 }{ {a}^{2} + 7a + 10} \times \frac{ {a}^{2} + 6a + 5}{ {a}^{2} + 5a + 4 } \\ = \frac{ {a} + 4 }{ (a + 2)(a + 5)} \times \frac{(a + 5)(a + 1)}{(a + 4)(a + 1)} \\ = \frac{1}{a + 2}\\\\ \frac{9m-4}{8}+\frac{3m+8}{8} \\=\frac{12m+4}{8}\\=\frac{3m-1}{2}\\\\\frac{4{x}^{2}}{2x-7}-\frac{49}{2x-7}\\=\frac{4{x}^{2}-49}{2x-7}\\=\frac{(2x-7)(2x+7)}{2x-7}\\=(2x+7)[/tex]

Please find attached photograph for your answer.

Hope it helps and sorry for delay.

Ver imagen Аноним